Biodegradable rifampicin-releasing coating of surgical meshes for the prevention of bacterial infections - Reinbold J; Hierlemann T; Urich L; Uhde AK; Müller I; Weindl T; Vogel U; Schlensak C; Wendel HP; Krajewski S (Dove Medical Press, 2017)
Jochen Reinbold,1 Teresa Hierlemann,1 Lukas Urich,1 Ann-Kristin Uhde,1 Ingrid Müller,2 Tobias Weindl,3 Ulrich Vogel,4 Christian Schlensak,1 Hans Peter Wendel,1 Stefanie Krajewski1 1Department of Thoracic and Cardiovascular Surgery, University Hospital Tübingen, Tübingen, 2Department of Pharmaceutical Engineering, Albstadt-Sigmaringen University of Applied Science, Albstadt, 3Aimecs® GmbH Medical Solutions, Pfarrkirchen, 4Institute of Pathology and Neuropathology, Tübingen, Germany Abstract: Polypropylene mesh implants are routinely used to repair abdominal wall defects or incisional hernia. However, complications associated with mesh implantation, such as mesh-related infections, can cause serious problems and may require complete surgical removal. Hence, the aim of the present study was the development of a safe and efficient coating to reduce postoperative mesh infections. Biodegradable poly(lactide-co-glycolide acid) microspheres loaded with rifampicin as an antibacterial agent were prepared through single emulsion evaporation method. The particle size distribution (67.93±3.39 µm for rifampicin-loaded microspheres and 64.43±3.61 µm for unloaded microspheres) was measured by laser diffraction. Furthermore, the encapsulation efficiency of rifampicin (61.5%±2.58%) was detected via ultraviolet–visible (UV/Vis) spectroscopy. The drug release of rifampicin-loaded microspheres was detected by UV/Vis spectroscopy over a period of 60 days. After 60 days, 92.40%±3.54% of the encapsulated rifampicin has been continuously released. The viability of BJ fibroblasts after incubation with unloaded and rifampicin-loaded microspheres was investigated using an MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, which showed no adverse effects on the cells. Furthermore, the antibacterial impact of rifampicin-loaded microspheres and mesh implants, coated with the antibacterial microspheres, was investigated using an agar diffusion model with Staphylococcus aureus. The coated mesh implants were also tested in an in vivo mouse model of staphylococcal infection and resulted in a 100% protection against mesh implant infections or biofilm formation shown by macroscopic imaging, scanning electron microscopy, and histological examinations. This effective antibacterial mesh coating combining the benefit of a controlled drug delivery system and a potent antibacterial agent possesses the ability to significantly reduce postoperative implant infections. Keywords: postoperative infections, drug delivery system, antibacterial implant coating, Staphylococcus aureus, antibiotic